Developmental Programming of Hypertension and Kidney Disease - Euming Chong; Ihor V. Yosypiv (International Journal of Nephrology)
A growing body of evidence supports the concept that changes in the intrauterine milieu during “sensitive” periods of embryonic development or in infant diet after birth affect the developing individual, resulting in general health alterations later in life. This phenomenon is referred to as “developmental programming” or “developmental origins of health and disease.” The risk of developing late-onset diseases such as hypertension, chronic kidney disease (CKD), obesity or type 2 diabetes is increased in infants born prematurely at <37 weeks of gestation or in low birth weight (LBW) infants weighing <2,500 g at birth. Both genetic and environmental events contribute to the programming of subsequent risks of CKD and hypertension in premature or LBW individuals. A number of observations suggest that susceptibility to subsequent CKD and hypertension in premature or LBW infants is mediated, at least in part, by reduced nephron endowment. The major factors influencing in utero environment that are associated with a low final nephron number include uteroplacental insufficiency, maternal low-protein diet, hyperglycemia, vitamin A deficiency, exposure to or interruption of endogenous glucocorticoids, and ethanol exposure. This paper discusses the effect of premature birth, LBW, intrauterine milieu, and infant feeding on the development of hypertension and renal disease in later life as well as examines the role of the kidney in developmental programming of hypertension and CKD.